Virulence of Entamoeba histolytica trophozoites. Effects of bacteria, microaerobic conditions, and metronidazole (The Rockefeller University Press, 1984)
The association of axenically grown trophozoites of Entamoeba histolytica strains HK-9 or HM-1:IMSS with various types of gram- negative bacteria for relatively short periods markedly increased their virulence, as evidenced by their ability to destroy monolayers of tissue-cultured cells. Interaction of trophozoites with bacteria that were heat inactivated, glutaraldehyde fixed, or disrupted by sonication, or bacteria treated with inhibitors of protein synthesis, did not augment amebic virulence. Lethally irradiated bacteria, however, retained their stimulative properties and trophozoites that ingested bacteria were protected from the toxic effects of added hydrogen peroxide. An increase in virulent properties of amebae was also found in experiments carried out under microaerobic conditions (5% O2, 10% CO2). The augmentation of amebic virulence due to association with bacteria was specifically blocked by metronidazole, but not by tetracycline or aminoglycosides, and the rate of metronidazole uptake in stimulated trophozoites was two to three times higher. The results obtained suggest that virulence of axenically grown E. histolytica trophozoites may depend to a considerable extent on the cell's reducing power. Both microaerobic conditions and the association with bacteria apparently stimulate the electron transport system of the ameba. Bacteria may function as broad range scavengers for oxidized molecules and metabolites through the contribution of enzymatic systems, components, or products.